Biocompatibility and preliminary clinical application of HA/HDPE nanocomposites synthetic auditory ossicle - 朱晒红 王国慧 赵颜忠 戚悠飞 周科朝 黄苏萍 李志友 黄伯云 (Transactions of Nonferrous Metals Society of China, 2006)
The biocompatibility of the hydroxyapatite/high density polyethtlene（HA/HDPE） nanocomposites synthetic auditory ossicle was evaluated, the percentage of S-period cells was detected by flow cytometry after L929 incubated with extraction of the HA/HDPE nanocomposites, titanium materials of clinical application as the control. Both of them were implanted in the animals and the histopathological evaluations were carried out, and the preliminary clinical trials about HA/HDPE nanocomposites synthetic auditory ossicles were also carried out. The statistical analysis show that there are no statistically significant differences between HA/HDPE test groups and control groups （P〉0.05）, which demonstrates that the HA/HDPE nanocomposites synthetic auditory ossicle has a good biocompatibility and clinical application outlook.